2014
DOI: 10.1016/j.ihj.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Off-pump coronary artery bypass grafting in India

Abstract: Off-pump Coronary Artery Bypass Grafting (OPCAB) is the latest innovation in cardiac surgery. However OPCAB is not adopted universally. Even there have been suggestions of abandoning OPCAB in a special report. In India, OPCAB has been successfully adopted across the board. There are various evidences which favor OPCAB and are discussed in this review. The purpose of this review is to put forward the perspective of the OPCAB surgeons of our country and critically look at the suggestion of abandoning OPCAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…OPCAB graft patency rates of Left Internal Mammary Artery (98.3%), Radial Artery (96%) and Saphenous Vein (91.2%) published in this study are excellent and far superior than both ONCAB and OPCAB graft patency rates of the recently published RCTs from the western world. The beneficial effects of dual anti-platelet therapy on OPCAB graft patency have been discussed in literature [4] and in this study too, Raghuram et al rightly used dual antiplatelet therapy immediately after OPCAB. However, I disagree with their viewpoint that maintaining activated clotting time (ACT) more than 350 seconds during OPCAB is mandatory.…”
Section: Opcab: the Future Of Surgical Coronary Revascularizationmentioning
confidence: 73%
See 3 more Smart Citations
“…OPCAB graft patency rates of Left Internal Mammary Artery (98.3%), Radial Artery (96%) and Saphenous Vein (91.2%) published in this study are excellent and far superior than both ONCAB and OPCAB graft patency rates of the recently published RCTs from the western world. The beneficial effects of dual anti-platelet therapy on OPCAB graft patency have been discussed in literature [4] and in this study too, Raghuram et al rightly used dual antiplatelet therapy immediately after OPCAB. However, I disagree with their viewpoint that maintaining activated clotting time (ACT) more than 350 seconds during OPCAB is mandatory.…”
Section: Opcab: the Future Of Surgical Coronary Revascularizationmentioning
confidence: 73%
“…Many studies published in international literature confirm this [4]. In a series of more than 600 consecutive unselected Indian patients, it was proven that complete revascularization can be better performed using OPCAB technique in spite of diffuse coronary artery disease (CAD), low ejection fraction or recent myocardial infarction without the anxiety of increasing cardiopulmonary bypass time or ischemic time [5].…”
Section: Opcab: the Future Of Surgical Coronary Revascularizationmentioning
confidence: 88%
See 2 more Smart Citations
“…On the other hand, in OPCAB the stabilizer can be reused after sterilization and the price is divided among several patients. Given to this and to a shorter ICU stay, it is reported that an OPCAB patient will generally pay a lower price for a CABG procedure (49). In Japan, OPCAB is slightly less common than in India but still prevails over ONCAB.…”
Section: Regional Variationsmentioning
confidence: 99%